(untitled) (Communications in Mathematical Research, 2021)
This paper deals with the existence of solutions to the p(t)-Laplacian equation with four-point boundary conditions. It is shown, by Leray-Schauder fixed point theorem and degree method, that under suitable conditions, solutions of the problem exist. The interesting point is that p(t) is a general function.